Analysis of Needs and Recommendations for Service Improvements at 2-Star Hotels through the Integration of SERVQUAL, Refined Kano, and TRIZ - Fazrin, Dea Aulia; Syahrullah, Yudi; Sofiana, Amanda; Nando, Fiky Two (STKIP Singkawang, 2025)
This study aims to analyse service needs, enabling hotel management to enhance the quality of hotel services. The method used to analyse customer needs integrates the Service Quality and Refined Kano methods to determine the attributes that must be prioritised and developed to improve hotel services. Proposed improvements to improve customer satisfaction using the TRIZ method. The sampling method employed was purposive sampling, a non-probability sampling technique. Using the service quality method, the study's results identified attributes that fell into the strong and weak categories. The study continued using the Kano Model method and received results for 3 Attractive category attributes, 8 Must-be category attributes, 6 One-dimensional category attributes, and 6 Indifferent category attributes. Next, Service Quality and Refined Kano integration were carried out to determine True Customer Needs. Eight attributes included in True Customer Needs must be prioritised in the High-valued, Adequate, and Critical categories. Attributes were analysed using the TRIZ method to identify proposed improvements for each priority set.